Numerical modelling of suspension high velocity oxy fuel (S-HVOF) thermal spray - Chadha, Sunil (2021)
Suspension high velocity oxy fuel (SHVOF) thermal spray is an emerging technology used to deposit nano and submicron particles onto the surface of a component to form dense coatings with a fine microstructure. Coatings are deposited onto components to improve their performance by modifying the components surface properties. Numerical models have been employed within the open literature to improve the understanding of the process. This thesis focuses on development of a new thermal spray technology, a hybrid nozzle, that allows for the deposition of a composite coating formed from two materials with drastically different properties. Oxygen sensitive materials such as graphene nanoplatelets degrade when exposed to oxygen at high temperatures. A radial injection allows for a reduction of the time the particles are exposed to oxygen at high temperatures. A physical shroud has been designed based upon the modelling work within this thesis to prevent mixing of ambient oxygen within the jet. The physical shroud is combined with a shrouding gas to delay the mixing of oxygen. A combination of a radial injection, a physical shroud and a shrouding gas allows for a lower oxygen content within the jet and a reduction of the residence time of the particles within the jet. The axial injection within the combustion chamber can be simultaneously used for injecting a feedstock containing ceramic particles. The combined radial and axial injection are expected to allow for a significant improvement in the deposition of composite coatings. The hybrid nozzle is a completely new concept which offers fundamental changes over the traditional SHVOF thermal spray design. Numerical models employed within the literature to predict the flow behaviour within SHVOF thermal spray have suffered from a number of flaws. The prior combustion models employed over predict the gas temperature within the combustion chamber when compared to the adiabatic flame temperature. Additionally, prior combustion models demonstrate unphysical species compositions away from the flame front. This thesis employs a robust treatment to model the combustion reaction within SHVOF thermal spray to better predict the combustion chamber temperature and species composition. This approach avoids the overprediction in the adiabatic flame temperature as seen with the global single step mechanism currently employed within the literature to model SHVOF thermal spray. Additionally, the numerical models to determine the heat transfer coefficient previously employed within the literature underpredict the particle temperatures by as much as 40 % when compared to experimental measurements. This thesis evaluates the effects of the Mach number and the Knudsen number on the Nusselt number to better predict the heat transfer coefficient for the suspension particles. The models are validated against ensembled averaged inflight particle temperature measurements obtained from the commercially available Accuraspray G4 diagnostic system. It is shown that accounting for Mach number effects better predicts the particle temperature however accounting for Knudsen number effects provides the most accurate prediction of the heat transfer to particles within suspension high velocity oxy fuel thermal spray. Finally, this thesis presents the first ever high-fidelity investigation into the combustion chamber for SHVOF thermal spray using a coupled volume of fluid and discrete particle model with the large eddy simulation scale resolving method. This multiscale approach provides a significant reduction in the computational cost over the standalone volume of fluid framework and a significantly higher fidelity over the standalone discrete particle model framework. The framework has been developed to expand the understanding within an SHVOF thermal spray combustion chamber; to characterise and inform the injection for use in lower fidelity models. From this approach more representative suspension injection conditions can be used for lower fidelity DPM - RANS methods. From the numerical modelling undertaken a modified injector design is proposed to reduce clogging within the combustion chamber.